Type 2 diabetes mellitus and cognitive decline in older adults in Germany: results from a population-based cohort - Xie, Kun; Perna, Laura; Schöttker, Ben; Kliegel, Matthias; Brenner, Hermann; Mons, Ute (BMC geriatrics, 2022)
A large body of evidence supports a link between type 2 diabetes mellitus (T2DM) and cognitive function, including dementia. However, longitudinal studies on the association between T2DM and decline of cognitive function are scarce and reported mixed results, and we hence set out to investigate the cross-sectional and longitudinal association between T2DM and global as well as domain-specific cognitive performance.